In everlasting fight against academic procrastination: The roles of classroom engagement and internal locus of control - Yen Ling Hui; Kususanto Ditto Prihadi; Najiya I. Arif; Sam X. Y. Yap; Melissa J. Chua; John Chen; Jia C. Chong; James L. H. Yeow (Institute of Advanced Engineering and Science, 2019)
This study aims to test the hypothesis that classroom engagement mediates the relationship between students’ internal locus of control and academic procrastination. As many as 302 students from a private university between 18 to 26 years of age were recruited to respond to Internal-External Locus of control Scale, Classroom Engagement Inventory, and Academic Procrastination scale. Bootstrapping analyses were conducted by utilizing PROCESS Macro model 4 in SPSS software, and the results showed that the mediator variable fully mediates the link between the predictor and outcome variables. In other words, the direct effect of internal locus of control on academic procrastination was no longer significant when controlling for classroom engagement. Further discussion, implications and suggestions were presented at the end of the article.